Lunasin-induced behavioural effects in mice: Focus on the dopaminergic system - Dzirkale, Zane; Rumaks, Juris; Svirskis, Simons; Mazina, Olga; Allikalt, Anni; Rinken, Ago; Jekabsons, Kaspars; Muceniece, Ruta; Klusa, Vija (Elsevier, 2013)
The present study for the first time is devoted to identify central effects of synthetic lunasin, a 43 amino acid peptide. A markedly expressed neuroleptic/cataleptic effect was observed at low (0.1–10 nmol/mouse) centrally administered doses in male C57Bl/6 mice. Lunasin considerably reduced the amphetamine hyperlocomotion but weakly apomorphine climbing behaviour. No influence on ketamine and bicuculline effects was observed. Binding assay studies demonstrated modest affinity of lunasin for the dopamine D1 receptor (Ki = 60±15 M). In a functional assay of cAMP accumulation on live cells lunasin antagonised apomorphine effect on D1 receptor activation (pEC50 = 6.1±0.3), but had no effect in cells expressing D2 receptors. The obtained data suggest that lunasin’s action at least in part is provided via dopaminergic D1 receptor pathways. However, other non-identified mechanisms (probably intracellular) may play an important role in lunasin’s central action. Nevertheless further studies of lunasin are promising, particularly taking into account a necessity for novel type of antipsychotic drugs
Keywords: Lunasin; Behaviour; Dopamine receptors; cAMP